Phosphorus flows on ships: Case study from the Baltic Sea. (May 2019) - Wilewska-Bien, Magda; Granhag, Lena; Jalkanen, Jukka-Pekka; Johansson, Lasse; Andersson, Karin
Material flow analysis is used to identify and quantify the flow of phosphorus (P) in ship-generated food waste and wastewater. Passenger, cruise, RoPax and cargo ships in the Baltic Sea were investigated in three scenarios: (1) if all waste is discharged to sea, (2) if all waste is disposed of ashore or (3) if the food waste fraction is disposed of ashore and wastewater is treated on-board. About 107 tonnes of P is generated annually in the waste streams, with highest contribution of approximately 62 tonnes (58%) from wastewater in the ship-category RoPax. Approximately 24 tonnes of P is contained in the food waste generated by the ships in the study. Forthcoming regulations over allowed nutrient concentrations in sewage will lead to 80% reduction in P from passenger ships and can reduce about 31 tonnes of P entering the Baltic Sea environment. If both sewage and grey water instead are offloaded in port reception facilities, about 76 tonnes of P-reduction to the sea can be reached. As most phosphorus recovery practices currently only are available on land it is recommended to direct the waste streams to port reception facilities for further treatment ashore.